X-ray study of Nd0.5Sr0.5MnO3 above and below the ferromagnetic metal-antiferromagnetic insulator spontaneous phase transition manganite structure - Eremenko, V.; Balakrishnan, G.; Kamenev, K. V.; Fink-Finowicki, J.; Sirenko, V.; Shvedun, M.; Shabakayeva, Yu.; Makedonska, N.; Gnatchenko, S.; Paul, D. McK (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The crystal structure of the manganite Nd0.5Sr0.5MnO3 is studied at temperatures T=300 and 77.3 K by means of an x-ray diffractometer. It is shown that the transition from the ferromagnetic metallic state to the antiferromagnetic insulating charge-ordered state is accompanied by a lowering of the symmetry of the structure from orthorhombic to monoclinic. The space-group symmetry of the orthorhombic and monoclinic phases is identified as Imma and P21 / m, respectively. Twinning of the crystal and the formation of a twin domain structure with coherent boundaries in the (00l) crystallographic planes are found.